Aromatic Amine Catalysts for the O2-Mediated Cross-Dehydrogenative Phenothiazination Reaction? - Nandi, Shiny; Paffen, Alina; Patureau, Frederic W. (Synlett, 2024)
Metal-free aromatic amines have been utilized recently as redox-active catalysts in various oxidative coupling reactions. In this study, we investigated a series of aromatic amines and their potential redox catalytic activity, in particular compared to our previously reported amino-Te(II) catalysts. The O2-mediated cross-dehydrogenative phenothiazination of phenols was utilized as a benchmark test reaction, as well as the O2-mediated cross-dehydrogenative coupling of indoles. We thus identified a proton sponge as an effective aromatic amine redox catalyst. It was moreover found that although the proton sponge displays clear catalytic activity, it is generally less active than previously reported phenotellurazine catalysts. The insights provided by this study should guide future research efforts for the development of innovative redox-catalyzed cross-dehydrogenative coupling reactions.
Keywords: redox catalysis; proton sponge; amine catalysis; tellurium catalysis; O2 activation; cross-dehydrogenative coupling